Transformation and movement of ammonium ion in soils of the Itaguaí series - Leal, Jair Rocha; Alvahydo, Roberto (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted on the sandy soils of the Itaguaí series to study the movement and transformation of NH4+ ions under natural conditions. In a randomized block design three plots were fertilized with ammonium sulfate at a basic rate of 700 kg/ha, and three plots maintained as controls. The plot area was kept free of vegetation during the 149 days of the experiment and the precipitation was recorded. Soil samples were collected at four depths (0-7 cm, 7-14 cm, 14-21 cm and 21-28 cm) during 7 different periods on each of the plots. The soils were analyzed for NH4+, NO3-, and soil moisture. It is concluded that no appreciable amounts of the ammoniacal form of nitrogen was lost through percolation, since the NH4+ ion reached the maximum depth of 14 cm at the end of approximately, two months, and all of the ammoniacal nitrogen was nitrified. The major portion of the added nitrogen was lost in the form of NO3- nitrogen. The effect of the ammoniacal fertilizer under the conditions of the experiment was present till four and half months.